1997
DOI: 10.1016/s0014-5793(97)00819-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rat brain calpastatin efficiency by post‐translational modifications

Abstract: Calpains, the thiol proteinases of the calciumdependent proteolytic system, are regulated by a natural inhibitor, calpastatin, which is present in brain tissue in two forms. Although both calpastatins are highly active on human erythrocyte calpain, only one form shows a high inhibitory efficiency with both rat brain calpain isozymes. The second calpastatin form is almost completely inactive against homologous proteinases and can be converted into an active one by exposure to a phosphoprotein phosphatase, also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 37 publications
(56 reference statements)
3
70
0
1
Order By: Relevance
“…It has been also demonstrated previously that both in vivo and in vitro -calpain seems to be involved in the inhibitor fragmentation, generating free active inhibitory domains, whereas m-calpain digests calpastatin producing inactive peptides (13)(14)(15). The different kinds of degradation accomplished by the two calpains is consistent with the hypothesis that fragmentation of calpastatin by -calpain, the first step of the inhibitor digestion process, corresponds to a local increase in active calpastatin species.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…It has been also demonstrated previously that both in vivo and in vitro -calpain seems to be involved in the inhibitor fragmentation, generating free active inhibitory domains, whereas m-calpain digests calpastatin producing inactive peptides (13)(14)(15). The different kinds of degradation accomplished by the two calpains is consistent with the hypothesis that fragmentation of calpastatin by -calpain, the first step of the inhibitor digestion process, corresponds to a local increase in active calpastatin species.…”
supporting
confidence: 86%
“…ural inhibitor protein calpastatin (13,42,43). An alternative exon splicing at the level of L-domain seems necessary to produce tissue-specific calpastatin molecules (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adachi et al (1991) showed that phosphorylation increased the proportion of CAST bound to membranes and Salamino et al (1997) demonstrated that phosphorylation decreased CAST inhibitory efficiency. Calpastatin phosphorylation could therefore influence proteolysis and ultimately have an effect on tenderness and other related meat quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether the 2% of membrane-bound calpastatin in bovine cardiac muscle (279) was phosphorylated, but membrane-bound calpastatin can inhibit the calpains as effectively as cytosolic calpastatin (280); hence, the physiological significance of membrane-associated calpastatin is unclear. In vitro phosphorylation of rat brain calpastatin by either PKA or PKC (382) or by PKC (13) has been reported to decrease its efficiency (increase the concentration required for half-maximal inhibition) in inhibiting either -or m-calpain. The PKA phosphorylation occurred in the NH 2 -terminal part of calpastatin, and the PKC phosphorylation occurred on Ser-13 of rat calpastatin (rat calpastatin lacks the XL domain, so numbering starts with Met-1 of the L-domain; Ref.…”
Section: B Properties Of Calpastatinmentioning
confidence: 99%